Definition and clinical evaluation of a recruiting airway pressure based on the specific lung elastance in anesthetized dogs. (July 2021) - Araos, Joaquin; Lacitignola, Luca; Acquafredda, Claudia; DiBella, Caterina; Stabile, Marzia; Guacci, Erica; Gleed, Robin; Grasso, Salvatore; Crovace, Antonio; Staffieri, Francesco
Abstract: Objective: To determine the specific lung elastance (SEL ) in anesthetized dogs and to evaluate the efficacy of a SEL -based recruiting airway pressure ( RP aw ) at improving global and regional lung aeration. Study design: Retrospective and prospective clinical study. Animals: A total of 28 adult dogs were included in the retrospective study and six adult dogs in the prospective study. Methods: Retrospective study: SEL and SEL -based RP aw were determined using previously published data. In mechanically ventilated dogs undergoing thoracic computed tomography (CT), SEL was calculated as Δ P L /(VT /EELV), where Δ P L is the driving transpulmonary pressure, VT is the tidal volume and EELV is the end-expiratory lung volume. The ratio of lung to respiratory system elastance (EL /Ers ) was determined. SEL and EL /Ers were used to calculate the SEL -based RP aw . Prospective study: dogs underwent thoracic CT at end-expiration and at end-inspiration using the SEL -based RP aw, and global and regional aeration was determined. For analysis of regional aeration, lungs were divided into cranial, intermediate and caudal regions. Regional compliance was also calculated. A p value <0.05 was considered significant. Results: The SEL and EL /Ers were 12.7 ± 3.1 cmH2 O and 0.54 ± 0.07, respectively. The SEL -based RP aw was 29.1 ± 7.6 cmH2 O. In the prospective study, the RP aw was 28.2 ± 1.3 cmH2 O. During RP aw, hyperinflation increased ( p = 0.0003) whereas poorly aerated ( p < 0.0001) and nonaerated ( p = 0.01) tissue decreased. Normally aerated tissue did not change ( p = 0.265). Regional compliance was higher in the intermediate ( p = 0.0003) and caudal ( p = 0.034) regions compared with the cranial region. Aeration did not differ between regions ( p > 0.05). Conclusions and clinical relevance: An SEL -based RP aw reduces poorly and nonaerated lung tissue in anesthetized dogs. In nonsurgical anesthetized dogs, an RP aw near 30 cmH2 O is effective at improving lung aeration.